ChemInform Abstract: Facile Preparation of Dehydrodigallic Acid and Its Derivative for the Synthesis of Ellagitannins. Issue 23 (10th June 2014) - Shioe, Kazuma; Ishikura, Shingo; Horino, Yoshikazu; Abe, Hitoshi
Abstract The synthesis of highly functionalized biaryl ether derivatives [cf.